A review of systematic reviews of the effectiveness of conservative interventions for rotator cuff tendinopathy. Issue 3 (4th March 2013) - Littlewood, Chris; May, Stephen; Walters, Stephen
Abstract Background Rotator cuff tendinopathy is common and a wide range of conservative interventions are currently used to treat this problem. The purpose of this review is to systematically review the systematic reviews that evaluate the effectiveness of conservative interventions for rotator cuff tendinopathy. Methods An electronic search of PEDro, MEDLINE and the Cochrane Library was undertaken and supplemented by hand and citation searching. The AMSTAR checklist was adopted for quality appraisal and a narrative synthesis was undertaken. Results Twenty‐six systematic reviews were retrieved. Methodological quality was variable. Exercise and multimodal physiotherapy appear to confer superior outcomes over no treatment or placebo, although the clinical significance of these results remains unclear. Surgery does not confer an additional benefit over exercise alone or multimodal physiotherapy. Combining manual therapy with exercise is not currently supported, neither is the use of corticosteroid injections or acupuncture. Other commonly prescribed interventions lack evidence of effectiveness. Conclusions Exercise and multimodal physiotherapy might be effective interventions for rotator cuff tendinopathy, although the clinical significance of this effect is unclear. This interpretation is drawn from systematic reviews comprising mainly small randomized controlled trials that frequently measure outcome in a heterogeneous manner, limiting the strength of any conclusions.